IMPLEMENTASI HUKUM PERTANGGUNGJAWABAN PEJABAT PEMBUAT AKTA TANAH DALAM PEMBUATAN AKTA JUAL BELI TANAH - Laia, Fariaman; Hulu, Klaudius Ilkam; Laia, Fianusman (LPPM Universitas Nias Raya, 2024)
In terms of buying and selling land, it is a common thing that is easily recognized by every community, but on the other hand, it must be noted that buying and selling land must see the completeness of the seller's files so that evidence of an authentic deed can be seen from the certificate or letter issued by the PPAT, to avoid legal personal in the future. This study aims to determine the implementation of the legal responsibility of land deed making officials in making land sale and purchase deeds. This study uses a normative legal research method with a conceptual and legislative approach. The results of the study show that by carrying out the sale and purchase before the PPAT, clear requirements are met (not dark legal acts, which are carried out secretly). The PPAT is responsible for checking the requirements for the validity of legal acts that the responsibility as a PPAT profession, in making a sale and purchase deed, a PPAT is expected and required to be more careful and issue a sale and purchase deed without ignoring the standardization of the issuance of a sale and purchase deed.